High purity nanoscale lithium sulfide, its preparation method and its uses

The described method addresses the challenges of achieving high purity and nanoscale lithium sulfide by purifying raw materials, employing nanoscale wet milling, and incorporating a demagnetization process, resulting in improved purity and performance while simplifying production.

JP2025511646APending Publication Date: 2025-04-16TIANQI LITHIUM GENESIS TECH (SHENZHEN) LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024557968
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-01-17
Filing Date
2023-11-22
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

Existing methods for preparing lithium sulfide fail to achieve high purity (>99.99%) and nanoscale particle sizes, leading to agglomeration, large particle sizes, and difficulties in large-scale production due to strict airtightness requirements.

Method used

A method involving the purification of hydrazine hydrate and lithium sources, followed by nanoscale wet milling, homogeneous reaction under inert conditions, and ball milling to achieve high purity nanoscale lithium sulfide, while incorporating a demagnetization process to reduce magnetic material content.

Benefits of technology

The method achieves high purity nanoscale lithium sulfide with particle sizes less than 1,000 nm, reduces magnetic material content to less than 50 ppb, eliminates the need for vacuum degassing, and simplifies large-scale production by reducing airtightness requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511646000001_ABST
    Figure 2025511646000001_ABST
Patent Text Reader

Abstract

The present invention relates to high-purity nano-scale lithium sulfide and its preparation method, which belongs to the technical field of all-solid-state lithium ion battery materials. The preparation method of the present invention includes the steps of raw material purification, nano-scale wet milling, homogeneous reaction and ball milling to obtain high-purity nano-scale lithium sulfide product. The high-purity nano-scale lithium sulfide and its preparation method of the present invention have high purity, excellent performance, simple operation and achieve good social and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to high-purity nanoscale lithium sulfide and its preparation method, which belongs to the technical field of all-solid-state lithium-ion battery materials. [Background technology]

[0002] In recent years, the new energy vehicle industry has developed rapidly, but challenges such as insufficient driving range, charging time, and safety have prevented further expansion of market share. Lithium-sulfur batteries and all-solid-state batteries are considered the most promising next-generation battery technologies due to their high energy density. Lithium sulfide can be used as the positive electrode active material of lithium-sulfur batteries and as the main raw material for synthesizing solid electrolytes, and has become a highly popular material in the field of secondary batteries. According to a report on all-solid-state lithium-ion batteries, based on the existing market size of lithium-ion batteries, the potential market size of lithium sulfide for all-solid-state batteries may reach tens of billions of yuan in the future, and the market shows great potential.

[0003] Lithium sulfide, an important component of sulfur-based solid electrolytes, affects the ionic conductivity of solid electrolytes and is one of the factors that determine the performance of all-solid-state batteries. Therefore, the quality requirements for lithium sulfide are becoming increasingly stringent. Recent related studies have also shown that the size of lithium sulfide particles has a significant impact on the performance of all-solid-state batteries, and it was reported in the international journal Nano Lett that sulfide electrolytes with particle sizes less than 1 μM are more stable when in contact with metallic lithium and can reduce the chemical and mechanical failure of solid electrolytes. A recent study from Tianjin University published in the Journal of Energy Chemistry found that micron-scale lithium sulfide used as the positive electrode of lithium-sulfur batteries has no electrochemical activity and is even more susceptible to mechanical damage due to volumetric fluctuations. In contrast, nanoscale lithium sulfide can overcome the above challenges. The high specific surface area provided by nanoscale lithium sulfide facilitates the lithiation / delithiation process, which is manifested as reduced electrical / ionic resistance, increased capacity, and improved performance due to reduced mechanical stress associated with volumetric changes. In addition, some industry insiders suggest that since magnetic substances have a certain impact on the performance of solid electrolytes, a demagnetization process needs to be introduced into the subsequent lithium sulfide preparation process to further reduce the content of magnetic substances.

[0004] China Patent Publication No. 112678781 discloses a method for preparing lithium sulfide. The specific steps of the preparation method are as follows: Crushing and mixing: The sulfur source and the lithium source are mixed and crushed, and hydrazine hydrate is added during the crushing process. When the addition is completed, the crushing is terminated to obtain the reaction raw material. Here, the sulfur source is sulfur powder, lithium thiosulfate or lithium sulfite, and the lithium source is lithium hydroxide, lithium thiosulfate or lithium sulfite. Vacuum degassing: The reaction raw material is placed in a vacuum degassing barrel, the vacuum degassing barrel is evacuated, and when the bubbles are removed, the vacuum state is maintained for 1 to 4 hours, and then the pressure is returned to normal pressure to obtain a lithium sulfide solution. Drying: The lithium sulfide solution is dried to obtain lithium sulfide. This method has the disadvantages that it is not possible to prepare high-purity (purity > 99.99%) lithium sulfide, and that the lithium sulfide product is easily agglomerated and has a large particle size due to the presence of a large amount of moisture in the reaction system. In addition, this preparation method requires vacuum degassing, which places strict requirements on the airtightness of the reactor body, making large-scale production difficult. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] China Patent Application Publication No. 112678781 Summary of the Invention [Means for solving the problem]

[0006] In order to solve the technical problem, the present invention provides a method for preparing high purity nano-scale lithium sulfide. The method for preparing high purity nano-scale lithium sulfide includes the following steps: A. Refining raw materials Purification of reducing agent: Purification of hydrazine hydrate, anhydrous hydrazine and / or hydroxylamine reducing agent is carried out to remove impurities and obtain high purity reducing agent. Purification of lithium source: Purifying the lithium source to obtain a high purity lithium source, said lithium source being battery grade lithium hydroxide monohydrate, anhydrous lithium hydroxide, high purity lithium oxide and / or battery grade lithium carbonate. b. Nanoscale wet milling: The high-purity reducing agent obtained in step a and the high-purity lithium source are weighed out so that the molar ratio is 1:1 to 3, and then uniformly mixed to obtain a high-purity lithium source slurry in which particles are uniformly dispersed on a nanoscale. c. Homogeneous reaction: high-purity sulfur powder is dissolved in the high-purity reducing agent obtained in step a to obtain a sulfur-containing slurry, and the sulfur-containing slurry and the high-purity lithium source slurry obtained in step b are simultaneously dropped into a reactor according to a chemical reaction ratio and mixed well, and reacted and dried under the protection of an inert atmosphere to obtain slightly aggregated high-purity lithium sulfide. d. Ball Milling: The slightly agglomerated high purity lithium sulfide obtained in step c is ball milled to obtain uniformly dispersed nanoscale high purity lithium sulfide product.

[0007] Here, in step a, When the lithium source is battery grade lithium hydroxide monohydrate or anhydrous lithium hydroxide, the lithium source is dissolved in high purity water to obtain a lithium salt solution, which is then dried and thermally decomposed to obtain anhydrous lithium hydroxide with a water content of <5%; When the lithium source is battery grade lithium carbonate, it is purified by carbonization and decomposition, If the lithium source is high purity lithium oxide, no purification is required; In the step a, when the lithium source is battery grade lithium hydroxide monohydrate or anhydrous lithium hydroxide, the concentration of the prepared lithium salt solution is Li2O:60-80g / L, and the solution is dried at a low temperature in vacuum at 75-90°C. When battery grade lithium carbonate is used as the raw material, water is added to the solution to form a slurry, and the slurry is purified by carbonization decomposition. When high purity lithium oxide is used as the raw material, no purification is required.

[0008] The purity of the high purity reducing agent is 4N, the purity of the battery grade lithium hydroxide monohydrate is in accordance with GB / T 26008-2020, the purity of the anhydrous lithium hydroxide is in accordance with YS / T 1568-2022, the purity of the high purity lithium oxide is in accordance with YS / T 968-2014, the purity of the battery grade lithium carbonate is in accordance with YS / T 582-2013, and the purity of the high purity sulfur powder is 4N.

[0009] Here, in step a, when the high-purity lithium source is battery-grade lithium hydroxide monohydrate, lithium hydroxide having a large particle size is heated to a temperature lower than its melting point in a vacuum or inert gas atmosphere, and an inert gas is passed through the lithium source until the content of residual water of crystallization in the lithium source produced is less than 5% by weight, thereby obtaining a dehydrated high-purity lithium source. This operation can obtain a lithium source having a content of residual water of crystallization of less than 5% by weight by controlling the drying temperature. The purpose is to improve the reaction activity and reduce the inclusion of moisture. Here, the inert atmosphere is a nitrogen or argon atmosphere, a mixed atmosphere of hydrogen and argon, or other atmosphere, and the heating temperature is 200 to 450°C.

[0010] Here, the nanoscale wet milling in step b is a method of crushing and mixing the raw materials by utilizing the impact of falling grinding bodies (such as zirconia balls or steel balls) and crushing by the grinding bodies and the inner wall of the ball mill.

[0011] Here, the mixing method in step b involves wet milling in a ball mill for 1 to 8 hours, and the ball milling rotation speed is 300 to 600 rpm.

[0012] Here, in step c, when the reducing agent is hydrazine hydrate and / or anhydrous hydrazine, the high-purity sulfur powder and the reducing agent are mixed to prepare a sulfur-containing solution in a molar ratio of 1:1-3, and when the reducing agent is hydroxylamine, the high-purity sulfur powder and the reducing agent are mixed to prepare a sulfur-containing solution in a molar ratio of 1:2-4, and the molar ratio of the high-purity lithium source slurry to the sulfur-containing solution is Li2O:S=1:1-3.

[0013] Here, in step c, the reaction is first carried out in a low-temperature environment, and then the temperature is raised to carry out the reaction. The reaction conditions in the low-temperature environment are a stirring speed of 100 to 300 rpm, a high-shear disperser speed of 2,000 r / min to 5,000 r / min, a temperature of 70 to 150°C, and a reaction time of 1 to 3 hours. The reaction conditions when the temperature is raised to carry out the reaction are a stirring speed of 300 to 500 rpm, a temperature of 200 to 450°C, and a reaction time of 1 to 3 hours.

[0014] Here, in the step d, the ball milling rotation speed is 300 to 600 rpm, and the ball milling time is 1 to 8 hours.

[0015] Here, in order to reduce the magnetic substance to less than 50 ppb, demagnetization is performed at least once in any one of steps a, b, c, and d, and the magnetic field strength of the demagnetization is 8,000 to 12,000 GS.

[0016] In order to solve the second technical problem, the present invention provides a high-purity nano-scale lithium sulfide prepared by the above-mentioned method for preparing high-purity nano-scale lithium sulfide, preferably, the high-purity nano-scale lithium sulfide has a particle size of less than 1,000 nm, a purity of 99.99% or more, and a magnetic substance content of less than 50 ppb.

[0017] To solve the third technical problem, the present invention provides an application of the above-mentioned high-purity nanoscale lithium sulfide in an all-solid-state battery, preferably the all-solid-state battery is a lithium-sulfur battery. Effect of the Invention

[0018] 1. The high purity nano-scale lithium sulfide and its preparation method of the present invention reduce the content of magnetic substances by introducing the demagnetization process, and in addition to improving the purity and performance of the raw materials, the vacuum degassing is no longer required, and the airtightness requirements of the equipment are relaxed, resulting in good economic benefits.

[0019] 2. The high purity nanoscale lithium sulfide and its preparation method of the present invention are achieved by first carrying out nanoscale wet milling of the raw materials, using a high shear disperser and controlling the process parameters, so that the primary particles of the obtained product reach nanoscale, and then carrying out secondary purification of the raw materials, so that the purity of the product reaches 4N. [Brief description of the drawings]

[0020] [Figure 1] A magnified scanning electron microscope image of the product obtained by the method for preparing high-purity nanoscale lithium sulfide according to the present invention. [Diagram 2] XRD diagram of the product obtained by the method for preparing high purity nano-scale lithium sulfide according to the present invention DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, the embodiments of the present invention will be described in detail with reference to specific examples, but those skilled in the art will understand that the following examples are used only to illustrate the present invention and should not be considered as limiting the scope of the present invention. In addition, unless specific conditions are specified in the examples, the examples will be carried out according to conventional conditions.

[0022] Example 1 (1) Purification of raw materials: 500 mL of commercially available anhydrous hydrazine (hydrazine) was weighed and vacuum distilled and purified in a draft chamber to obtain high-purity hydrazine. 500 g of battery-grade lithium hydroxide monohydrate was weighed and dissolved in high-purity water to prepare a lithium solution with a Li2O concentration of 60 g / L. After evaporation and centrifugation, the obtained wet product was vacuum-dried at 75°C for 1 hour to obtain high-purity lithium hydroxide monohydrate raw material.

[0023] (2) Dehydration of Feedstock: The high purity lithium hydroxide monohydrate feedstock obtained in step (1) was heated to 200° C. under a nitrogen atmosphere until anhydrous lithium hydroxide feedstock with a water content of less than 5% was produced.

[0024] (3) Nanoscale wet milling: Anhydrous hydrazine solution was added to a ball mill so that the molar ratio of Li2O:anhydrous hydrazine was 1:1, and ball milling was performed in the ball mill at a rotation speed of 300 rpm for 8 hours to obtain a nanoscale anhydrous lithium hydroxide slurry.

[0025] (4) Homogeneous reaction: High-purity sulfur powder and anhydrous hydrazine are mixed to prepare a sulfur-containing slurry in a molar ratio of 1:1. The sulfur-containing slurry and lithium hydroxide slurry are simultaneously dropped into a reactor equipped with an anchor stirrer and a high-shear disperser through a peristaltic pump and mixed well, and the molar ratio of the raw materials is Li2O:S=1:1. Under the protection of an inert atmosphere, the high-shear emulsifying disperser is turned on and the rotation speed is set to 2,000r / min, while stirring is started at 100r / min. After reacting at 70°C for 3 hours, the temperature is increased to 450°C and the stirring speed is increased to 300r / min. The high-shear disperser is turned off and dried for 1 hour, and nanoscale high-purity lithium sulfide, which is a slightly aggregated primary particle, is obtained.

[0026] (5) Ball milling: The agglomerated raw materials were placed in a ball mill and ball milled at a rotation speed of 300 r / min for 5 hours to obtain high-purity nanoscale lithium sulfide.

[0027] (6) Demagnetization: The ball-milled high-purity lithium sulfide was fed into an electromagnetic demagnetizer for demagnetization, and the magnetic field strength was set at 8,000GS to obtain a high-purity lithium sulfide product with magnetic matter less than 50ppb. The SEM and XRD patterns of the obtained product are shown in Figure 1 and Figure 2, respectively.

[0028] Example 2 (1) Purification of raw materials: 500 mL of commercially available anhydrous hydrazine (hydrazine) was weighed and vacuum distilled and purified in a draft chamber to obtain high-purity hydrazine. 500 g of anhydrous lithium hydroxide was weighed and dissolved in high-purity water to prepare a lithium solution with a Li2O concentration of 70 g / L. After evaporation and centrifugation, the obtained wet product was vacuum dried at 80°C for 1 hour to obtain high-purity lithium hydroxide monohydrate raw material.

[0029] (2) Dehydration of Feedstock: The high purity lithium hydroxide monohydrate feedstock obtained in step (1) was heated to 300° C. under nitrogen atmosphere until anhydrous lithium hydroxide feedstock with a water content of less than 5% was produced.

[0030] (3) Nanoscale wet milling: Anhydrous hydrazine solution was added to a ball mill so that the molar ratio of Li2O:anhydrous hydrazine was 1:2, and ball milling was performed in the ball mill at a rotation speed of 600 rpm for 1 hour to obtain a uniformly dispersed nanoscale anhydrous lithium hydroxide slurry.

[0031] (4) Homogeneous reaction: Prepare a sulfur-containing slurry by mixing high-purity sulfur powder and anhydrous hydrazine so that the molar ratio is 1:1. The sulfur-containing slurry and lithium hydroxide slurry are simultaneously dropped into a reactor equipped with an anchor stirrer and a high-shear disperser through a peristaltic pump and mixed well, and the molar ratio of the raw materials is Li2O:S=1:2. Under the protection of an inert atmosphere, turn on the high-shear emulsifying disperser, set the rotation speed to 5,000r / min, and start stirring at 300r / min. After reacting at 150°C for 1 hour, increase the temperature to 200°C and increase the stirring rotation speed to 500r / min. Turn off the high-shear disperser and dry for 3 hours to obtain nanoscale high-purity lithium sulfide, which is a slightly aggregated primary particle.

[0032] (5) Ball milling: The agglomerated raw materials were placed in a ball mill and ball milled at a rotation speed of 600 r / min for 1 hour to obtain high-purity nanoscale lithium sulfide.

[0033] (6) Demagnetization: The ball-milled high-purity lithium sulfide was fed into an electromagnetic demagnetizer for demagnetization, and the magnetic field strength was set at 12,000GS to obtain a high-purity lithium sulfide product with magnetic matter less than 50ppb. The purity data of this product is shown in Table 1.

[0034] Example 3 (1) Purification of raw materials: 500 mL of commercially available anhydrous hydrazine (hydrazine) was weighed and vacuum distilled and purified in a draft chamber to obtain high-purity hydrazine. 500 g of anhydrous lithium hydroxide was weighed and dissolved in high-purity water to prepare a lithium solution with a Li2O concentration of 80 g / L. After evaporation and centrifugation, the obtained wet product was vacuum dried at 85°C for 1 hour to obtain high-purity lithium hydroxide monohydrate raw material.

[0035] (2) Dehydration of Feedstock: The high purity lithium hydroxide monohydrate feedstock obtained in step (1) was heated to 450° C. under nitrogen atmosphere until anhydrous lithium hydroxide feedstock with a water content of less than 5% was produced.

[0036] (3) Nanoscale wet milling: Anhydrous hydrazine solution was added to a ball mill so that the molar ratio of Li2O:anhydrous hydrazine was 1:3, and ball milling was performed in the ball mill at a rotation speed of 500 rpm for 4 hours to obtain a nanoscale anhydrous lithium hydroxide slurry.

[0037] (4) Demagnetization: High-purity sulfur powder and anhydrous hydrazine were mixed in a molar ratio of 1:3 to prepare a sulfur-containing slurry. The sulfur-containing slurry and the anhydrous lithium hydroxide slurry were each sent to an electromagnetic demagnetizer via a peristaltic pump for demagnetization, and the magnetic field strength was set to 10,000 GS.

[0038] (5) Homogeneous reaction: The demagnetized sulfur-containing solution and lithium hydroxide slurry were simultaneously dropped into a reactor equipped with an anchor stirrer and a high-shear disperser via a peristaltic pump and mixed well, and the molar ratio of the raw materials was Li2O:S=1:3. Under the protection of an inert atmosphere, the high-shear emulsifying disperser was turned on, the rotation speed was set to 3000r / min, and stirring was started at 200r / min. After reacting at 100°C for 2 hours, the temperature was increased to 300°C and the stirring speed was increased to 400r / min. The high-shear disperser was turned off, and the mixture was dried for 2 hours to obtain nanoscale high-purity lithium sulfide, which is a slightly aggregated primary particle.

[0039] (6) Ball milling: The agglomerated raw materials were placed in a ball mill and ball milled at a rotation speed of 600 r / min for 1 hour to obtain a high-purity nanoscale lithium sulfide product. The purity data of this product are shown in Table 1.

[0040] Example 4 (1) Purification of raw materials: 500 mL of commercially available hydrazine hydrate (hydrazine hydrate) was weighed and vacuum distilled and purified in a draft chamber to obtain high-purity hydrazine hydrate. 500 g of lithium hydroxide monohydrate was weighed and dissolved in high-purity water to prepare a lithium solution with a Li2O concentration of 70 g / L. After evaporation and centrifugation, the obtained wet product was vacuum dried at 80 °C for 1 hour to obtain high-purity lithium hydroxide monohydrate raw material.

[0041] (2) Demagnetization: The high-purity lithium hydroxide monohydrate raw material obtained in the above process was sent to an electromagnetic demagnetizer to be demagnetized, and the magnetic field strength was set at 10,000 GS.

[0042] (3) Dehydration of Feedstock: The high purity lithium hydroxide monohydrate feedstock obtained in step (1) was heated to 300° C. under nitrogen atmosphere until anhydrous lithium hydroxide feedstock with a water content of less than 5% was produced.

[0043] (4) Nanoscale wet milling: Hydrazine hydrate solution was added to a ball mill so that the molar ratio of Li2O:hydrazine hydrate was 1:2, and ball milling was performed for 1 hour at a rotation speed of 600 rpm to obtain a uniformly dispersed nanoscale anhydrous lithium hydroxide slurry.

[0044] (5) Homogeneous reaction: Prepare a sulfur-containing slurry by mixing high-purity sulfur powder and hydrazine hydrate so that the molar ratio is 1:1. The sulfur-containing slurry and lithium hydroxide slurry are simultaneously dropped into a reactor equipped with an anchor stirrer and a high-shear disperser through a peristaltic pump and mixed well, and the molar ratio of the raw materials is Li2O:S=1:2. Under the protection of an inert atmosphere, turn on the high-shear emulsifying disperser, set the rotation speed to 5,000r / min, and start stirring at 300r / min. After reacting at 150°C for 1 hour, increase the temperature to 200°C and increase the stirring rotation speed to 500r / min. Turn off the high-shear disperser and dry for 3 hours to obtain nanoscale high-purity lithium sulfide, which is a slightly aggregated primary particle.

[0045] (6) Ball milling: The agglomerated raw materials were placed in a ball mill and ball milled at a rotation speed of 600 r / min for 1 hour to obtain a high-purity nanoscale lithium sulfide product. The purity data of this product are shown in Table 1.

[0046] Example 5 (1) Purification of raw materials: 500 g of lithium hydroxide monohydrate was weighed out in a draft chamber and dissolved in high-purity water to prepare a lithium solution with a Li2O concentration of 70 g / L. After evaporation and centrifugation, the obtained wet product was vacuum-dried at 80°C for 1 hour to obtain high-purity lithium hydroxide monohydrate raw material.

[0047] (2) Dehydration of Feedstock: The high purity lithium hydroxide monohydrate feedstock obtained in step (1) was heated to 300° C. under nitrogen atmosphere until anhydrous lithium hydroxide feedstock with a water content of less than 5% was produced.

[0048] (3) Nanoscale wet milling: A commercially available 4N hydroxylamine reducing agent was added to a ball mill so that the molar ratio of LiO:hydroxylamine was 1:2. The mixture was then ball milled at 600 rpm for 1 hour to obtain a uniformly dispersed nanoscale anhydrous lithium hydroxide slurry.

[0049] (4) Homogeneous reaction: Prepare a sulfur-containing slurry by mixing high-purity sulfur powder and hydroxylamine so that the molar ratio is 1:2. The sulfur-containing slurry and lithium hydroxide slurry are simultaneously dropped into a reactor equipped with an anchor stirrer and a high-shear disperser through a peristaltic pump and mixed well, and the molar ratio of the raw materials is Li2O:S=1:2. Under the protection of an inert atmosphere, turn on the high-shear emulsifying disperser, set the rotation speed to 5,000r / min, and start stirring at 300r / min. After reacting at 150°C for 1 hour, increase the temperature to 200°C and increase the stirring rotation speed to 500r / min. Turn off the high-shear disperser, dry for 3 hours, and obtain nanoscale high-purity lithium sulfide, which is a slightly aggregated primary particle.

[0050] (5) Ball milling: The agglomerated raw materials were placed in a ball mill and ball milled at a rotation speed of 600 r / min for 1 hour to obtain a high-purity nanoscale lithium sulfide product.

[0051] (6) Demagnetization: The ball-milled high-purity lithium sulfide was fed into an electromagnetic demagnetizer for demagnetization, and the magnetic field strength was set at 12,000GS to obtain a high-purity lithium sulfide product with magnetic matter less than 50ppb. The purity data of this product is shown in Table 1.

[0052] Example 6 (1) Refining of raw materials: 500 g of battery grade lithium carbonate was weighed out in a draft chamber, dissolved in high purity water to form a slurry, and high purity lithium carbonate was obtained by carbonization decomposition method.

[0053] (2) Nanoscale wet milling: A commercially available 4N hydroxylamine reducing agent was added to a ball mill so that the molar ratio of LiO:hydroxylamine was 1:2, and the mixture was ball milled at 600 rpm for 1 hour to obtain a uniformly dispersed nanoscale high-purity lithium carbonate slurry.

[0054] (3) Homogeneous reaction: High-purity sulfur powder and hydroxylamine are mixed to prepare a sulfur-containing slurry in a molar ratio of 1:2. The sulfur-containing slurry and high-purity lithium carbonate slurry are simultaneously dripped into a reactor equipped with an anchor stirrer and a high-shear disperser through a peristaltic pump and mixed well, and the molar ratio of the raw materials is Li2O:S=1:4. Under the protection of an inert atmosphere, the high-shear emulsifying disperser is turned on and the rotation speed is set to 5,000r / min, while stirring is started at 300r / min. After reacting at 150°C for 1 hour, the temperature is increased to 200°C and the stirring speed is increased to 500r / min. The high-shear disperser is turned off and dried for 3 hours, resulting in nanoscale high-purity lithium sulfide, which is a slightly aggregated primary particle.

[0055] (4) Ball milling: The agglomerated raw materials were placed in a ball mill and ball milled at a rotation speed of 400 r / min for 3 hours to obtain a high-purity nanoscale lithium sulfide product.

[0056] (5) Demagnetization: The ball-milled high-purity lithium sulfide was fed into an electromagnetic demagnetizer for demagnetization, and the magnetic field strength was set at 10,000GS to obtain a high-purity lithium sulfide product with less than 50ppb of magnetic material. The purity data of this product is shown in Table 1.

[0057] Example 7 (1) Nanoscale wet milling: High-purity lithium oxide raw material and commercially available 4N hydroxylamine reducing agent were added to a ball mill so that the molar ratio of LiO:hydroxylamine was 1:2. The mixture was ball milled at 600 rpm for 1 hour to obtain a uniformly dispersed nanoscale high-purity lithium oxide slurry.

[0058] (2) Homogeneous reaction: Prepare a sulfur-containing slurry by mixing high-purity sulfur powder and hydroxylamine so that the molar ratio is 1:2. The sulfur-containing slurry and high-purity lithium oxide slurry are simultaneously dropped into a reactor equipped with an anchor stirrer and a high-shear disperser through a peristaltic pump and mixed well, and the molar ratio of the raw materials is Li2O:S=1:3. Under the protection of an inert atmosphere, turn on the high-shear emulsifying disperser, set the rotation speed to 3,000r / min, and start stirring at 300r / min. After reacting at 150°C for 1 hour, increase the temperature to 200°C and increase the stirring rotation speed to 500r / min. Turn off the high-shear disperser, dry for 3 hours, and obtain nanoscale high-purity lithium sulfide, which is a slightly aggregated primary particle.

[0059] (3) Ball milling: The agglomerated raw materials were placed in a ball mill and ball milled at a rotation speed of 400 r / min for 3 hours to obtain a high-purity nanoscale lithium sulfide product.

[0060] (4) Demagnetization: The ball-milled high-purity lithium sulfide was fed into an electromagnetic demagnetizer for demagnetization, and the magnetic field strength was set at 12,000GS to obtain a high-purity lithium sulfide product with magnetic matter less than 50ppb. The purity data of this product is shown in Table 1. [Table 1]

[0061] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims the benefit of and priority to Chinese patent application CN 2023100614553, filed on January 17, 2023, which is incorporated in its entirety by reference and for all other purposes.

Claims

1. 1. A method for preparing high purity nanoscale lithium sulfide, comprising the steps of: a. Refining raw materials Purification of reducing agent: Purification of hydrazine hydrate, anhydrous hydrazine and / or hydroxylamine reducing agent is carried out to remove impurities and obtain high purity reducing agent. Purification of lithium source: Purify the lithium source to obtain a high purity lithium source, said lithium source being battery grade lithium hydroxide monohydrate, anhydrous lithium hydroxide, high purity lithium oxide and / or battery grade lithium carbonate. b. Nanoscale wet milling: The high-purity reducing agent and the high-purity lithium source obtained in step a are weighed out so that the molar ratio is 1:1 to 3, and then uniformly mixed to obtain a high-purity lithium source slurry in which particles are uniformly dispersed on a nanoscale. C. homogeneous reaction: high purity sulfur powder is dissolved in the high purity reducing agent obtained in step a to obtain sulfur-containing slurry, and the sulfur-containing slurry and the high purity lithium source slurry obtained in step b are simultaneously dropped into a reactor according to chemical reaction ratio and mixed well, and reacted and dried under the protection of inert atmosphere to obtain slightly aggregated high purity lithium sulfide. d. Ball Milling: The slightly agglomerated high purity lithium sulfide obtained in step c is ball milled to obtain uniformly dispersed nanoscale high purity lithium sulfide product.

2. In step a, When the lithium source is battery grade lithium hydroxide monohydrate or anhydrous lithium hydroxide, the lithium source is dissolved in high purity water to obtain a lithium salt solution, which is then dried and thermally decomposed to obtain anhydrous lithium hydroxide with a water content of <5%; When the lithium source is battery grade lithium carbonate, it is purified by carbonization and decomposition, If the lithium source is high purity lithium oxide, no purification is required; When the lithium source in step a is battery grade lithium hydroxide monohydrate or anhydrous lithium hydroxide, the concentration of the prepared lithium salt solution is Li 2 The method for preparing high purity nanoscale lithium sulfide according to claim 1, characterized in that the O content is 60-80g / L, and the drying is performed at a low temperature in vacuum at 75-90°C. When battery grade lithium carbonate is used as the raw material, water is added to make a slurry, and then the slurry is purified by carbonization decomposition. When high purity lithium oxide is used as the raw material, no purification is required.

3. The method for preparing high purity nano-scale lithium sulfide according to claim 1 or 2, characterized in that at least one demagnetization is carried out to reduce the magnetic material to less than 50 ppb, and the magnetic field strength of the demagnetization is 8,000-12,000 GS.

4. The method for preparing high purity nano-scale lithium sulfide according to claim 1, characterized in that the mixing method in step b is to carry out wet milling in a ball mill for 1 to 8 hours, and the ball milling rotation speed is 300 to 600 rpm.

5. The method for preparing high-purity nanoscale lithium sulfide according to claim 1 or 2, characterized in that the homogeneous reaction is carried out in a high shear disperser, the rotation speed of the high shear disperser is 2,000 r / min to 5,000 r / min, and the homogeneous reaction is carried out under conditions of a temperature of 70 to 150°C and a stirring rotation speed of 100 to 300 rpm for 1 to 3 hours, and then heated to 200 to 450°C and reacted at a stirring rotation speed of 300 to 500 rpm for 1 to 3 hours.

6. In step c, when the reducing agent is hydrazine hydrate and / or anhydrous hydrazine, the high-purity sulfur powder and the reducing agent are mixed to prepare a sulfur-containing solution in a molar ratio of 1:1-3; when the reducing agent is hydroxylamine, the high-purity sulfur powder and the reducing agent are mixed to prepare a sulfur-containing solution in a molar ratio of 1:2-4; and the molar ratio of the high-purity lithium source slurry to the sulfur-containing solution is Li 2 The method for preparing high purity nano-scale lithium sulfide according to claim 1, characterized in that O:S=1:1-3.

7. High-purity nano-scale lithium sulfide prepared by the method for preparing high-purity nano-scale lithium sulfide according to any one of claims 1 to 6.

8. 8. The high purity nanoscale lithium sulfide of claim 7, having a particle size of less than 1,000 nm, a purity of 99.99% or greater, and less than 50 ppb of magnetic material.

9. Use of the high purity nanoscale lithium sulfide according to claim 7 or 8 in an all-solid-state battery.

10. The use according to claim 9, characterized in that the all-solid-state battery is a lithium-sulfur battery.

Citation Information

Patent Citations

  • Preparation method and device of high-purity lithium sulfide

    CN105016310A

  • Method for preparing sulfide electrolyte by using nanocrystalline Li2S

    CN111816911A

  • Preparation method of lithium sulfide

    CN112678781A

  • KR20220118574A